1981
DOI: 10.1002/aic.690270419
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenolysis and hydrogenation of dibenzothiophene catalyzed by sulfided CoO‐MoO3/γ‐Al2O3: The reaction kinetics

Abstract: P n = roots of Eq. 8 P = total pressure in system 9 = adsorbed-phase concentration expressed on an intra-9* = equilibrium value of 9 9", 9-= initial and final steady values of 9 9nr = saturation value of 9 in Langmuir equation 9 s = fractional coverage (39/ 9m)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
75
0
17

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(97 citation statements)
references
References 17 publications
(14 reference statements)
5
75
0
17
Order By: Relevance
“…Due to the great importance of HDS units, different researchers have concentrated on various aspects of this process [5][6][7][8][9][10][11]. As kinetic and conversion determination studies, Feredous et al [5] studied the hydrodenitrogenation and hydrodesulfurization of heavy gasoil derived from bitumen by employing NiMo/Al 2 O 3 catalyst containing boron (B).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the great importance of HDS units, different researchers have concentrated on various aspects of this process [5][6][7][8][9][10][11]. As kinetic and conversion determination studies, Feredous et al [5] studied the hydrodenitrogenation and hydrodesulfurization of heavy gasoil derived from bitumen by employing NiMo/Al 2 O 3 catalyst containing boron (B).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has shown that at certain conditions, the DBT kinetic closely resembles that of an overall behavior of DBTs in a light oil fraction (Steiner, et al 2002) .…QÉOE »àjÈc …õØM πeÉY been reported. The reaction was shown to follow a pseudo-first-order kinetics and both parallel and consecutive reaction networks were identified (Girgis, et al 1991;Farag, et al 1997;Wang, et al 2004;Pille, et al 1994;Broderick, et al 1981). When the reaction of DBT was tested on CoMo/MCM-41, a pseudo-first-order kinetic model was found to represent the experimental data better than a Langmiur-Hinshelwood model.…”
Section: Introductionmentioning
confidence: 99%
“…In general, deep hydrodesulfurization of dibenzothiophenes over heterogeneous catalysts proceeds through two reaction pathways. One is hydrogenation (HYD) pathway, involving aromatic ring saturation and the other is a hydrogenolysis pathway via direct C-S bond cleavage, which is also called the direct desulfurization (DDS) pathway [34,35]. For production of clean fuels with low sulfur level, the effects of inhibitors, especially aromatic and nitrogen compounds, should be also considered and investigated.…”
Section: Subtask 31: Desulfurization and Denitrogenationmentioning
confidence: 99%